混业经营 ：中国金融业的经营趋势、模式选择及风险防范 = Universal banking and China's banking system - 相勇 Xiang, Yong (2008)
This dissertation analyzes the pros and cons of universal banking in general and makes a conclusion that China’s financial reform should apply universal banking, considering both the current international and domestic situations of the Chinese financial services industry.